Prescription pattern and effectiveness of antihypertensive drugs in patients with aortic dissection who underwent surgery - Liao, Kuang-Ming; Shen, Chuan-Wei; Huang, Yun-Hui; Lu, Chun-Hui; Lai, Hsuan-Lin; Chen, Chung-Yu (Frontiers in Pharmacology, 2023)
Background: Surgical patients with aortic dissection often require multiple antihypertensive drugs to control blood pressure. However, the prescription pattern and effectiveness of antihypertensive drugs for these patients are unclear. We aimed to investigate the prescription pattern and effectiveness of different classes of antihypertensive drugs in surgical patients with aortic dissection. Methods: Newly diagnosed aortic dissection patients who underwent surgery, aged >20 years, from 1 January 2012 to 31 December 2017 were identified. Patients with missing data, in-hospital mortality, aortic aneurysms, or congenital connective tissue disorders, such as Marfan syndrome, were excluded. Prescription patterns of antihypertensive drugs were identified from medical records of outpatient visits within 90 days after discharge. Antihypertensive drugs were classified into four classes: 1) β-blockers, 2) calcium channel blockers (CCBs), 3) renin–angiotensin system, and 4) other antihypertensive drugs. Patients were classified according to the number of classes of antihypertensive drugs as follows: 1) class 0, no exposure to antihypertensive drugs; 2) class 1, antihypertensive drugs of the same class; 3) class 2, antihypertensive drugs of two classes; 4) class 3, antihypertensive drugs of three classes; or 5) class 4, antihypertensive drugs of four classes. The primary composite outcomes included rehospitalization associated with aortic dissection, death due to aortic dissection, and all-cause mortality. Results: Most patients were prescribed two (28.87%) or three classes (28.01%) of antihypertensive drugs. In class 1, β-blockers were most commonly used (8.79%), followed by CCBs (5.95%). In class 2, β-blockers+CCB (10.66%) and CCB+RAS (5.18%) were the most common drug combinations. In class 3, β-blockers + CCB+RAS (14.84%) was the most prescribed combination. Class 0 had a significantly higher hazard of the composite outcome (HR, 2.1; CI, 1.46–3.02; p < 0.001) and all-cause mortality (HR, 2.34; CI, 1.56–3.51; p < 0.001) than class 1. There were no significant differences in hazards for rehospitalization associated with aortic dissection among classes. Conclusion: Among operated patients with type A aortic dissection, no specific type of antihypertensive drug was associated with a better outcome, whereas among those with type B aortic dissection, the use of β-blockers and CCBs was related to a significantly lower risk of the composite outcome.